O Artesão de si mesmo: um estudo sobre o processo de criação do ator Claudio Barros no espetáculo “Solo de Marajó” em Belém do Pará - ROCHA, Diego Augusto Pereira da (2018)
The present thesis is devoted to the study of the creative process of the actor. The work developed by the actor Claudio Barros is used as the subject for the physical construction of the characters of the spectacle „Solo de Marajó‟ (Marajó‟s land) from the perspective of the craftsman-actor, word proposed by me in this thesis. Through the concept of the craftsmanactor, I also propose that the actor is „his own craftsman‟. For the development of the research I use as the main theoretical source the method of the physical actions developed by Jerzy Grotowski. As a result, it has been found that the procedures used by the actor Claudio Barros can be considered as one of an actor „who is his own craftsman‟, which stimulates possible researches regarding the concept of craftsman-actor.